COVID-19 Pandemic: Analysis of Possible Scenarios for the Development of the Epidemic in Russia - S. V. Borisevich; T. E. Sizikova; V. N. Lebedev (Вестник войск РХБ защиты)
The COVID-19 pandemic posed many questions to world health. They could be satisfactorily answered only after a thorough study. During the initial period of the COVID-19 pandemic (early January 2020), it was considered a local outbreak of emergent coronavirus infection with an undetermined possibility of person-to-person transmission. However, on March 11, the World Health Organization (WHO) upgraded the status of the COVID-19 outbreak from epidemic to pandemic. The aim of this article was to analyze possible scenarios of the development of COVID-19 epidemics in Russia. COVID-19 infection occurs mainly in the beginning stage of the disease, when patients are not yet diagnosed. This is the fundamental difference between COVID-19 and SARS or MERS, in which patients become contagious after onset of symptoms of the disease. Based on the study of dynamics of changes in certain epidemiological characteristics, the epidemic in Russia was compared in this article with the same epidemics in China, Italy, Germany and the United States. The authors came to the conclusion, that the COVID-19 epidemic in Russia was different from the above mentioned epidemics, because the capital region (Moscow and Moscow region), the largest center of transport communications, became the epicenter of the epidemic in Russia. They considered different variants of epidemic development in Russia, depending on the intensity of ongoing anti-epidemic measures. To describe the spread of the epidemic, the SIR model (Susceptible Infected Recovered) proposed by Scottish epidemiologists W.O. Kermack and A.G. McKendrick was used. Based on the data obtained, it turned out to be possible to tentatively determine the final date of the active phase of the COVID-19 epidemic (after which it is possible to register only a limited number of cases of the disease). This date should come about 6 weeks after the completion of the plateau phase. The beginning of the plateau phase was early May 2020, and the end of the plateau phase should be mid June 2020. The estimated completion date should be August 8–25, 2020. The total number of people with a confirmed diagnosis could be 991–1122 thousand.